Repeated-sprint training at 5000-m simulated altitude in preparation for the world rugby women`s sevens series: Too high? - Brocherie, F.; Racinais, S.; Cocking, S.; Townsend, N.; Couderc, A.; Piscione, J.; Girard, O. (Medicine & Science in Sports & Exercise, 2023)
Purpose The objective of this study is to investigate the effectiveness of novel repeated-sprint training in hypoxia (RSH) protocol, likely maximizing hypoxic stimulus (higher than commonly used) while preserving training quality (interset rest in normoxia).